Agilitas Organisasi: Meningkatkan Kepuasan Kerja Dan Komitmen Organisasi Tenaga Keperawatan Di Ruang Rawat Inap Pasien Covid-19 - Mikaria Gultom (Jurnal Doktor Manajemen (JDM), 2022)
The Covid-19 pandemic has affected all aspects of people's lives and the world in a short time. The medical work environment dealing directly with patients is very stressful, especially for nurses who have to be in the inpatient room for 24 hours continuously. The purpose of this study was the extent to which hospital organizational agility could increase job satisfaction and organizational commitment of nurses working in inpatient room COVID-19 patients. This research method is a quantitative research method with data processing tools using the SmartPLS version 3.0. The research data was obtained from an online questionnaire using google form with a non-probability sampling technique, namely a convenience sampling technique (accidental sampling). The respondents of this study were 110 nurses who served in the Covid-19 inpatient service section at the Sentra Medika Group Hospital domiciled in West Java province which was appointed as a Covid-19 referral hospital by the Governor of West Java. The results showed that the direct effect coefficient of organizational agility on organizational commitment was 0.207, job satisfaction on organizational commitment was 0.484, and the indirect effect coefficient of organizational agility on organizational commitment through job satisfaction was 0.234. Thus, it can be concluded that organizational agility has a positive and significant effect on organizational commitment mediated by job satisfaction.